Identification of the Biosynthetic Pathway of Glycine Betaine That Is Responsible for Salinity Tolerance in Halophilic Thioalkalivibrio versutus D301 - Liu, Mengshuang; Liu, Hui; Mei, Fangtong; Yang, Niping; Zhao, Dahe; Ai, Guomin; Xiang, Hua; Zheng, Yanning (Frontiers in Microbiology, 2022)
Thioalkalivibrio versutus D301 has been widely used in the biodesulfurization process, as it is capable of oxidizing hydrogen sulfide to elemental sulfur under strongly halo-alkaline conditions. Glycine betaine contributes to the increased tolerance to extreme environments in some of Thioalkalivibrio species. However, the biosynthetic pathway of glycine betaine in Thioalkalivibrio remained unknown. Here, we found that genes associated with nitrogen metabolism of T. versutus D301 were significantly upregulated under high-salt conditions, causing the enhanced production of glycine betaine that functions as a main compatible solute in response to the salinity stress. Glycine betaine was synthesized by glycine methylation pathway in T. versutus D301, with glycine N-methyltransferase (GMT) and sarcosine dimethylglycine N-methyltransferase (SDMT) as key enzymes in this pathway. Moreover, substrate specificities of GMT and SDMT were quite different from the well characterized enzymes for glycine methylation in halophilic Halorhodospira halochloris. Our results illustrate the glycine betaine biosynthetic pathway in the genus of Thioalkalivibrio for the first time, providing us with a better understanding of the biosynthesis of glycine betaine in haloalkaliphilic Thioalkalivibrio.